The Net-Enabled Business Innovation Cycle and the Evolution of Dynamic Capabilities - ZAHRA, Shaker A. (Institutional Knowledge at Singapore Management University, 2002)
Wheeler's Net-Enabled Business Innovation Cycle (NEBIC) integrates IS and strategy research to offer an interesting and timely perspective on value creation. We extend Wheeler's theoretical propositions, highlighting the interplay between strategy, IS, and entrepreneurship in a quest for competitive advantage. This interplay is crucial to the creation of the dynamic capabilities that enable companies to gain an advantage through NEBIC. The importance of opportunity recognition and absorptive capacity in bringing about the changes that make NEBIC viable is also highlighted.